Residual kinematic deviations of the shoulder during humeral elevation after conservative treatment for mid-shaft clavicle fractures - Hung, Li-Wei; Lu, Hsuan-Yu; Chen, Tsan-Yang; Wang, Ting-Ming; Lu, Tung-Wu (Frontiers in Bioengineering and Biotechnology, 2024)
Despite residual functional deficits clinically observed in conservatively treated mid-shaft clavicle fractures, no study has reported a quantitative assessment of the treatment effects on the kinematics of the shoulder complex during functional movement. Using computerised motion analysis, the current study quantified the 3D residual kinematic deviations or strategies of the shoulder complex bones during multi-plane elevations in fifteen patients with conservatively treated mid-shaft clavicle fractures and fifteen healthy controls. Despite residual clavicular malunion, the patients recovered normal shoulder kinematics for arm elevations up to 60° in all three tested planes. For elevations beyond 60°, normal clavicle kinematics but significantly increased scapular posterior tilt relative to the trunk was observed in the patient group, leading to significantly increased clavicular protraction and posterior tilt relative to the scapula (i.e., AC joint). Slightly different changes were found in the sagittal plane, showing additional changes of increased scapular upward rotations at 90° and 120° elevations. Similar kinematic changes were also found on the unaffected side, indicating a trend of symmetrical bilateral adaptation. The current results suggest that shoulder kinematics in multi-plane arm elevations should be monitored for any compromised integrated motions of the individual bones following conservative treatment. Rehabilitation strategies, including muscle strengthening and synergy stability training, should also consider compensatory kinematic changes on the unaffected side to improve the bilateral movement control of the shoulder complex during humeral elevation.